Calcified Aneurysm of the Splenic Vein. Issue 1 (12th December 2022) - Leroij, Olivier; Bernard, Philippe; Vanhoenacker, Filip
Teaching Point: A thrombosed calcified aneurysm of the splenic vein is a rare complication of pancreatitis.